Exercise, training, and neutrophil function - Smith, J. A.; Pyne, D. B. (Exercise Immunology Review, 1997)
Although neutrophils are critical to host defense, they are also involved in the pathology of various inflammatory diseases. Neutrophils, representing 60% of circulating leukocytes in human subjects, are readily accessible to experimental investigation. Discrete aspects of, neutrophil function can be quickly and accurately assessed in vitro using a variety of techniques that involve assessment of intracellular and extracellular functional activities. Moderate exercise has variable effects on neutrophil function, but intense exercise is potentially immunosuppressive. Endurance training also suppresses most neutrophil functions chronically. A greater understanding of some fundamental aspects of neutrophil function and the uncovering of newly defined roles underlines potential applications in general and sports medicine. However, the practical value of this knowledge for monitoring the health and training programs of elite athletes requires further clarification. The current knowledge of neutrophil and immune functional measurements has not progressed to an extent that routine profiling in athletes can be used diagnostically.